DETERMINAN KEPUASAN KEUANGAN DENGAN BERBASIS LITERASI KEUANGAN PENGGUNA DOMPET DIGITAL DANA PADA MAHASISWA UNIVERSITAS PERWIRA PURBALINGGA - Yuliasari, Diajeng Indah; Fitriana, Aning; Tyas, Karunia Zuraidaning (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
Basically every human being will feel satisfaction and happiness if someone has a good financial condition. The more satisfied a person is with their financial condition, the more satisfied and happy that person will be. This research aims to determine the effect of financial knowledge, financial attitudes and financial behavior on financial satisfaction. The population in this study were all students at Perwira University, Purbalingga. Data collection with a sampling technique that is purposive sampling. The samples criteria used are University of Perwira Purbalingga students in the 2019-2022 class year and students who use Dana digital wallets. The number of samples used were 109 respondents. Based on the results of this reasearch, partially obtained that financial knowledge and financial attitudes have a significant effect on financial satisfaction while financial behavior has an insignificant effect on financial satisfaction. Simultaneously, financial knowledge, financial attitudes and financial behavior jointly or simultaneously have an influence on financial satisfaction.